Design and Simulation of Hiding Message Encrypted using Pseudo Random Number and Sequential Encoding - Gitaffa, Sabah A. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this paper, a hiding encrypted message using pseudo random number generator and sequential encoding is proposed. This algorithm can provide better security of hiding information in image. The main emphasis in mine results will be on visual image quality and also the peak signal to noise ratio (PSNR) value which is a measure of quality of embedding.  The results of statistical analyses like average difference, PSNR and MSE indicate high security and suitability of the proposed scheme. The obtained result shows the peak signal to noise ratio is 79dB. The programming language MATLAB is used for implementing the proposed algorithm.